A canopy photosynthesis model to predict the dry matter production of cocksfoot pastures under varying temperature, nitrogen and water regimes. - Peri, Pablo Luis (2003)
Daily net canopy photosynthesis (Pn) of cocksfoot (Dactylis glomerata L.) was predicted for combinations of temperature, herbage nitrogen (N) concentration and water status from the integration of models of leaf photosynthesis of the light-saturated photosynthetic rate (Pmax), photosynthetic efficiency (a) and the degree of curvature (h) of leaf light-response curves. The effect on Pn, maximum Pn (Pn max) and the optimum leaf area index (LAI at Pn max) was examined when any one of these factors was limiting. The ranges that gave the optimum values of Pn (Pn max ¼ 30Æ8–33Æ5 g CO2 m)2 d)1) for temperature (19–22°C) and N concentration (40–50 g N kg)1 DM) were smaller than those for net leaf photosynthesis. Also, Pn fell to 0 at a lower level of water stress (pre-dawn leaf water potential, wlp ¼ )12Æ5 bar) than for Pmax. The canopy photosynthesis model was then used to compare predicted and measured dry matter (DM) production for cocksfoot pastures grown under a diverse range of environmental conditions with field data from New Zealand and Argentina. To predict DM production leaf area index and leaf canopy angle were included from field measurements. The model explained about 0Æ85 of the variation in cocksfoot DM production for the range of 6Æ5–134 kg DM ha)1 d)1. The canopy model overestimated the DM production by 0Æ10 which indicates that a further Pmax function for leaves of different ages and a partitioning sub-model may be needed to improve predictions of DM production.